Computational Techniques for Automotive Antenna Simulations - Bogdanov, Faik; Jobava, Roman; Karkashadze, David; Tsereteli, Paata; Gheonjian, Anna; Yavolovskaya, Ekaterina; Schleicher, Detlef; Ullrich, Christoph; Tazi, Hicham (IntechOpen, 2011)
None